Justice and freedom in Leibniz - Carrera, Randal (2020)
This research defends the thesis that in Leibniz´s philosophy, both justice and freedom have an evident metaphysical grip, conveyed in the role of Divinity as a reference for human action. At first, the relationship between divine and human justice raised by Leibniz is addressed. Subsequently, the subject of freedom is deepened, particularly in the relation to free will and freedom of indifference. Finally, some conclusions are outlined regarding the contribution of these categories to current political thought.